Defense Policy Shaping and Security Governance: The Role and Impact of Defense Industry and Military Contractors - Aris Sarjito; Nora Lelyana (Dealings Foundation Institute, 2024)
This research explores the pivotal role of defense contractors in shaping defense policy and their significant impact on national security dynamics. Using qualitative research methods, with an emphasis on secondary data analysis, the study synthesizes findings from government reports, academic literature, and industry analyses. Key findings reveal the considerable influence of defense contractors’ lobbying activities on defense budget allocations and procurement policies, often redirecting resources toward projects that align with their technological expertise and profit motives. Additionally, defense contractors play a crucial role in shaping defense research and development priorities, driving innovation in areas such as cybersecurity, missile defense systems, and unmanned technologies. Ethically, the revolving door phenomenon between defense contractors and government officials raises concerns about potential conflicts of interest, undermining impartial decision-making and public trust. This research offers a comprehensive understanding of the strategic implications of contractor influence on defense policy, highlighting the need for greater transparency, accountability, and balanced competition in defense procurement. By illuminating these dynamics, the study contributes to policy discussions aimed at promoting ethical governance and ensuring the integrity of national security.